PENINGKATAN AKTIVITAS BELAJAR SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING PENDIDIKAN KEWARGANEGARAAN KELAS V - Hariyati, Hariyati; Salimi, Asmayani; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to improve students' learning activities using the model of Problem Based Learning in class V learning Citizenship Education Public Elementary School 20 South Pontianak. The research method is descriptive, with the form of classroom action research (PTK) and besifat collaborative. Subjects in this study were all fifth grade students of State Elementary School 20 South Pontianak totaling 30 people. The results showed that an increase in students' learning activities using the model of Problem Based Learning in learning Citizenship Education in Public Elementary School fifth grade 20 South Pontianak as evidenced by the results of the calculation in the first cycle count total average 41.62% and the second cycle total price -rata arithmetic 86.10%, this shows that from the first cycle to the second cycle increased by 44.48%.Â Â Keywords : Problem Based Learning, Student Activty.